State Promotion, Technological Capabilities, and Industrial Competitiveness: Differences Between Brazil and Argentina in The Automotive Value Chain - Dulcich, Federico Martín (2025)
The automotive value chain has traditionally been significant in Brazil and Argentina, and encouraged by specific incentives. The aim of this research is to analyse the differences regarding promotion policies of this value chain in these two countries, focusing on those oriented towards technological capabilities and, hereafter, to see their effects in terms of production, technology, and foreign trade. The methodology will be focused on the analysis of variables relevant to the scope of study. The results show that, unlike Argentina, Brazil has incorporated incentives for the development of technological capabilities in policies aimed at the automotive value chain. This resulted in Brazil's greater innovation efforts and results in the sector, a favourable gap in terms of productivity, and greater international competitiveness of the automotive value chain. In addition, it plays a leading role in the technological development of ethanol-fuelled engines and has a greater diffusion of electric vehicles than Argentina. These divergent trajectories demonstrate the relevance of public policy to promote the development of technological capabilities.